2016
DOI: 10.5897/jen2015.0145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some botanicals and Trichoderma harzianum against root-knot nematode (Meloidogyne incognita (Kofoid and White) Chit wood) in tomato

Abstract: Root-knot nematode, Meloidogyne incognita (Kofoid and White) Chit wood) is one of the major constraints for the successful cultivation of tomato (Lycopersicon esculentum Mill.) in Ethiopia. Among different management strategies, biological control is important in the light of increased awareness of environmental and human health hazards. Therefore, the present study was conducted to evaluate the effect of different locally available botanicals and an antagonistic fungus, Trichoderma harzianum to control root-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…This might have caused the fresh root weight of the control treatment to decrease. This finding was similar to Belay et al, (2019). Ahmad et al, 2007b andSiddiqui, 2006 were also reported that organic additives were effective in reducing RKN infestation and enhance various plant growth parameters and biomass.…”
Section: Effect Of Vermicompost and Moringa Leaf Powder On Growth Par...supporting
confidence: 83%
“…This might have caused the fresh root weight of the control treatment to decrease. This finding was similar to Belay et al, (2019). Ahmad et al, 2007b andSiddiqui, 2006 were also reported that organic additives were effective in reducing RKN infestation and enhance various plant growth parameters and biomass.…”
Section: Effect Of Vermicompost and Moringa Leaf Powder On Growth Par...supporting
confidence: 83%
“…This implies that each pathogen (Fusarium or Meloidogyne spp.) could cause significant wilt disease in African garden egg everything being equal, as has been variously reported in the literature (Safikhani et al, 2013;Ndifon et al, 2015;Feyisa et al, 2016;USDA, 2016;Göze Özdemir et al, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…According to the study by Kapil and Kapoor (2012), Wheat bran, Gandapana, and farm yard manure were the next most common places to find mass proliferation of Trichoderma spp. Feyisa et al (2016) used Gandapana in conjunction with T. harzianum successfully control the root-knot nematode in tomato.…”
Section: Growth Of T Harzianum After 1 St Week Of Inoculationmentioning
confidence: 99%